Heterogeneous Catalysis of C–O Bond Cleavage for Cellulose Deconstruction: A Potential Pathway for Ethanol Production. (20th February 2014) - Crews, Kristy; Reeves, Crystal; Thomas, Porsha; Abugri, Daniel; Russell, Albert; Curry, Michael L.
Abstract : Due to difficulty deconstructing the linkages between lignin, hemicellulose and cellulose during the conversion of cellulose to sugar, the commercial production of cellulosic ethanol is limited. This can be overcome by using a high surface-area metal catalyst. In this study, high surface-area metal NPs were synthesized using 20 mM of chloroplatinic acid and cobalt chloride prepared in THF with 0.1 mM of generation four poly(amido)amine (PAMAM) terminated dendrimer (G4-NH2 ) prepared in methanol and stirred for 2 hours under nitrogen. Subsequently, Pt +2 and Co +2 ions were reduced to metal zero via introduction of sodium borohydride and centrifuged for complete separation. The resulting product was heated for 2.5 hours at 200°C. After cooling, 2.0 grams of crushed peanut shells was added to 40 mL of distilled tert-butyl methyl ether along with the separated metal nanocatalyst and refluxed on condenser at 20% for 24 hours. UV-Vis and XRD analyses show the formation of Pt and Co nanoparticles using dendrimer templating methodology. Both TLC and HPLC show that, upon introduction of the metal catalyst into the suspension of "cellulose" in TBME, separation of the cellulose into small molecules is evident. That is, release of sugar molecules via C–O bond cleavage is facilitated by the formed nanocatalysts.